Acupoint stimulation for alcohol use disorder: A systematic review and meta-analysis. Issue 1 (6th January 2023) - Chen, Huishan; Feng, Jiaxin; Chen, Li; Huang, Jiarong; Zhang, Peiming; Chen, Chen; Lu, Liming; Tang, Chunzhi
Abstract : Background: To assess the effect of acupoint stimulation for Alcohol use disorders (AUD). Methods: AUD is a complex disease that threatens the health of the global population. Acupoint stimulation, a sort of therapy applying stimulation on acupoints to produce a therapeutic effect without side effects, has been widely used in AUD patients, but its efficacy remains controversial. Electronic databases (the Cochrane Library, EMBASE, PubMed, CNKI, VIP, Wan-Fang) were systematically searched for randomized controlled trials (RCTs) on acupoint stimulation for AUD from database inception to September 30, 2022. A meta-analysis was performed using Review Manager 5.4 software. Continuous data (scales) were expressed as mean differences (MDs) or standardized mean difference (SMD) with 95% confidence intervals (95% CI). Study methodological quality was assessed according to the Cochrane risk-of-bias tool for trials. The grading of recommendations assessment, development and evaluation was used to assess the certainty of evidence for outcomes. Results: A total of 16 RCTs with 1097 participants were included. Compared to psychotherapy or drug therapy alone, the combination of acupoint stimulation and other sorts of therapies presented advantages in alleviating alcohol craving (SMD = –1.09, 95% CI = –1.40 to –0.77, df = 2, P < .00001, grading of recommendations assessment, development and evaluation very low certainty), (SMD = –2.25, 95% CI = –3.17 to –1.34, df = 3, P < .00001, low certainty) and the severity of alcohol withdrawal symptoms (MD = –1.21, 95% CI = –2.32 to –0.1, df = 2, P = .03, low certainty), as well as improving anxiety (MD = –3.41, 95% CI = –4.06 to –2.76, df = 4, P < .00001, very low certainty) and depression levels (MD = –3.27, 95% CI = –4.92 to –1.62, df = 4, P = .0001, very low certainty) on patients with AUD. In addition, a greater effect was also found with the 4-week treatment courses in reducing craving (SMD = –2.18, 95% CI = –2.61 to –1.75, P < .00001, low certainty). Conclusion: Acupoint stimulation and its combined therapy may better relieve AUD symptoms effectively and the treatment duration should be set at more than 2 weeks. However, due to the low-quality of the included RCTs, high-quality studies are needed to further confirm it in the future.